Impact of Negative Decisions on Mental Health among College and University Students - Nayab Islam; Saira Majid; Muhammad Abdullah; Malaika Younas; Atif Rasool (Research Journal of Psychology, 2025)
The purpose of the study is to explore the intricate relationship between negative decisions and the mental health of college and university students. The correlation research design will be used for this study. The sample of the study will comprise N=300, evenly distributed between men (n=150) and women (n=150) in a university setting that will be selected ensuring the inclusion and exclusion criteria. Participants were selected through random sampling. The decision-making questionnaire (DMQ) was developed by Paul T. Coster (1998) and consists of 21 items, General health questionnaire (GHQ) was developed by David Goldberg (1994), and consisted of items 12. The finding aims to uncover the impact of negative experiences affects same as males and females. It is hypothesized that there will be a significant relationship between negative decision-making and mental health. Or there is a significant positive relationship between bad experiences or mental health among university or college students. The findings have significant implications for institutions to prioritize the students’ decision-making strategies or create a supportive environment to enhance their well-being to test these hypotheses Pearson moment correlation or t-test will measure Data will analyzed using the SPSS 20.0 version.